Phosphorus control as an effective strategy to adapt soybean to drought at the reproductive stage: evidence from field experiments across northeast China. (28th January 2015) - Zheng, H.F.; Chen, L.D.; Yu, X.Y.; Zhao, X.F.; Ma, Y.; Ren, Z.B.
Abstract Drought stress during the reproductive stage is one of the most important constraints on growth and productivity of soybean. There is compelling evidence that physiological and molecular approaches can effectively improve drought resistance in soybean, but strategies derived from soil management are poorly documented, especially under field conditions. In this study, we combined data from field experiments and used multivariate regression analyses to investigate factors determining soybean yield variability over two growing seasons with drought stress during the reproductive stage. Phosphorus application and soil available phosphorus explained a significant proportion of the variation in soybean yield under drought stress. As a whole, soybean fields that received adequate P supply had greater yields than those that did not. However, excessive P application significantly decreased soybean yield. These results suggest that P control is critical to mitigate soybean yield losses resulting from drought at the reproductive stage.